Effective Targeted Chemoprophylaxis of Recurrent Liver Echinococcosis with Haplotype CYP1A2F1*A/A: a Clinical Case - V. S. Panteleev; M. A. Nartaylakov; M. I. Lukmanov; G. I. Lukmanova (Креативная хирургия и онкология, 2020)
Background. One of the main longterm quality criteria for treatment and prevention of echinococcosis is postoperative relapse, which rate varies widely within 3–54% between medical facilities. The genetic traits of recurrent liver echinococcosis comprise an important subject of research into its etiopathogenetic factors for  an effective prognosis of cyst relapse and treatment personalisation.Materials and methods. Bashkir State Medical University (Ufa, Russia) provided facilities to study targeted  chemoprophylaxis efficacy in a case of relapsed liver echinococcosis with haplotype CYP1A2F1*A/A (AA) and the  UM phenotype of ultrarapid albendazole sulfoxidetoalbendazole sulfone metaboliser.Results and discussion. The clinical case presented illustrates the rationale behind personalised  chemoprevention of recurrent echinococcosis with albendazole based on genotyping data. Genotyping allows  detection of an ultrafast metaboliser haplotype in blood implicating a rapid degradation of administered albendazole, reduced antiparasitic impact of drug therapy and more feasible relapse, in contrast with a normal metaboliser phenotype.Conclusion. A successful secondary prevention of relapsed echinococcosis suggests the efficacy of personalising  albendazolebased chemoprophylaxis of recurrent echinococcosis with genotyping data.